2016
DOI: 10.1080/17518423.2016.1247923
|View full text |Cite
|
Sign up to set email alerts
|

Long-term motor, functional, and academic outcome following childhood ischemic and hemorrhagic stroke: A large rehabilitation center-based retrospective study

Abstract: Childhood stroke leads to severe and long lasting motor, functional, cognitive, and academic impairments, in a population of children admitted in a rehabilitation department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…As in previous studies, the analysis of these routinely collected clinical data demonstrate a heterogeneity, even within this more severe group. Overall, we present a reduction in the complexity of care needs and an increase in functional independence, which concurs with previous findings (Galvin et al., 2011; Yvon et al., 2018). While analysis of the data has shown that those with a hemispheric stroke had a higher level of independence than those with a global stroke, the numbers in these subgroups are small and further collaborative research is necessary across rehabilitation centres using commonly agreed measures to understand more about the outcomes in this group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As in previous studies, the analysis of these routinely collected clinical data demonstrate a heterogeneity, even within this more severe group. Overall, we present a reduction in the complexity of care needs and an increase in functional independence, which concurs with previous findings (Galvin et al., 2011; Yvon et al., 2018). While analysis of the data has shown that those with a hemispheric stroke had a higher level of independence than those with a global stroke, the numbers in these subgroups are small and further collaborative research is necessary across rehabilitation centres using commonly agreed measures to understand more about the outcomes in this group.…”
Section: Discussionsupporting
confidence: 93%
“…It is estimated that of the children who survive a stroke, half will face long-term neurological disability and functional limitations (Mackay and Steinlin, 2019). As a result, full participation in everyday social, educational and family life may be severely compromised, with the effects becoming more apparent over time (Ganesan, 2013; Greenham et al., 2018; McKevitt et al., 2019; Shepherd, 2012; Yvon et al., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…419 In a longer-term study of 82 children with hemorrhagic stroke at a median follow-up of 43 months, 40% were receiving special education. 420…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a rehabilitation centre-based retrospective study focused on the long-term outcome of 128 children after childhood AIS and HS. In general, they saw better motor neurological, functional and academic outcomes after HS (vs AIS) at time of discharge from the rehabilitation department 26. However, at time of discharge (median time since the stroke of 4.7 months), 59.3% of children with HS showed some degree of motor deficit and 35.8% required special education after a median follow-up period of 43 months.…”
Section: Discussionmentioning
confidence: 90%